Correlations Between Final‐Year Dental Students' Performance on Knowledge‐Based and Clinical Examinations. Issue 12 (1st December 2017) - Ali, Kamran; Jerreat, Matthew; Zahra, Daniel; Tredwin, Christopher
Abstract : Dental students are assessed using a range of methods in their final‐year examinations. The aim of this study was to explore the correlations and predictive value of final‐year dental students' performance on knowledge‐based and clinical assessments. Examination data related to applied dental knowledge (ADK), exit case presentation (CP), and integrated structured clinical examination (ISCE) assessments for five consecutive cohorts of final‐year students at one U.K. dental school from 2011–12 to 2015–16 were collated. The relationships between the scores produced by each assessment were investigated to explore the relative contributions of each to the understanding of students' abilities across the domains. The study utilized data from all 304 students: 147 (48.4%) females and 157 (51.6%) males. Significant positive correlations were found between ISCE and ADK performance (r(391)=0.42, p<0.001) as well as between ISCE and CP (r(391)=0.44, p<0.001). In addition, both ADK performance and CP performance were significant predictors (at p<0.001) of ISCE performance. This study provides important information about the relationship between these students' performance across knowledge (ADK) and clinical (ISCE and CP) domains and highlights their predictive value. Further research is required to establish if these findings can be generalized and to explore the correlations between performance of dental students before and after graduation.